Public Services Based On e-Government in Digital Age - Weningsih, Sri; Sulaiman, Adhi Iman; Chusmeru, Chusmeru; Adi, Tri Nugroho (Technium Social Sciences Journal, 2022)
The development of information and communication technology in the era of globalization, democratization, and decentralization has become a necessity as well as a challenge, especially for local governments in the development of communication for public services and community empowerment. The research used a qualitative case study method, with data collection through documentation, interviews, observations, and Focus Group Discussions (FGD). The research subjects were chosen purposively, namely local governments in four district governments in the southern region of Central Java in Indonesia, academics, observers, and digital media practitioners. The study used Cross Case Analysis to find the diversity, uniqueness, and depth of cases. The results of the study indicate that (1) Public services are important and strategic to be implemented through information and communication technology media in the form of e-Government to improve public services that are efficient, effective, participatory, responsive, and have transparency of information as well as budget accountability and implementation of development programs. (2) The government needs to anticipate the information technology gap so that it requires digital media literacy in improving the competence of human resources in government institutions, educational institutions, and social also business economics.